LATE DEATH AND INFRINGEMENT OF REGISTRATION DEADLINES: AN ANALYSIS IN LIGHT OF LAW 6.015/73 (REMUNOM, 2024)
This article aims to analyze Law 6.015/73, known as the Public Records Law, but specificallythe deadlines for death registration. In short, death registration, in particular, is essential for the legalvalidation of acts carried out after the death of an individual, since untimely registration can lead toseveral legal and administrative complications. The controversy lies in the way in which the rigidity oflegal deadlines affects the families of the deceased, prolonging suffering and worsening their economiccondition. Therefore, the objective of this research is to analyze the provisions of Law 6.015/73 relatingto late death registration, with the purpose of understanding their impacts and proposing regulatoryreforms that make legal deadlines more flexible, as well as ensuring that death registration is carriedout in an accessible manner, ensuring rights such as death pension and other benefits. Based on theseanalyses, the methodology used will be theoretical, through bibliographical research that will involvethe analysis of legislation, doctrines and academic dissertations related to the topic.